PENGEMBANGAN MEDIA PEMBELAJARAN BIOLOGI BERBASIS WEBSITE BERDASARKAN PEMBELAJARAN BERDIFERENSIASI PADA MATERI PENCEMARAN LINGKUNGAN - Mardin, Herinda; Dama, Lilan; M. Hasan, Ani; Maryati Yusuf, Frida; Latjompoh, Masra; Hayati, Nur (Jurnal Biogenerasi, 2024)
This research aims to develop website-based biology learning media on environmental pollution material based on differentiated learning for students. This type of research is development research, adapting the ADDIE development model including the stages of analysis, design, develop, implementation and evaluation. Development research was carried out to obtain website-based learning media regarding environmental pollution that is valid, so that it is suitable for use as learning media in high schools. The research results show that first, website-based biology learning media on environmental change material is included in very valid criteria based on expert validator assessments (content/material and construct) so that it can be used in the learning process at SMA Negeri 3 Gorontalo City.